(untitled) (LSP International Journal, 2020)
The importance of active learning and higher order thinking skills among students at higher learning institutions have steered lecturers to employ the flipped classroom approach in their classes. The move is hoped to assist students to become active recipients of knowledge and break away from the traditional learning method where knowledge is only imparted by lecturers. A study was conducted to investigate: (1) the TESL students’ ability to research and present their findings related to a teaching method via group posters when the flipped classroom approach is utilized in their Methodology in TESL 1 subject, and (2) their views on the feasibility of using flipped classroom approach for other TESL subjects. This study had adopted the mixed method approach in which an interview guide was used to address the first research question and a questionnaire was used to address the second research question. From the interview, it is found that majority of the TESL students had managed to research the teaching method assigned to them, had understood what they were reading, and were able to present the teaching method in the form of a poster. From the questionnaire data, it was found that majority of the TESL students agreed the flipped classroom approach can be implemented for other TESL subjects although a few of them felt that it might only be suitable for certain topics or subtopics as they were afraid of inaccurate knowledge being transferred if there is no proper guidance from the lecturer. Nevertheless, for this study, it can be concluded that the flipped classroom approach had enhanced the students’ understanding of the given topic, and it is feasible for other TESL subjects.